Native Species of Sapotaceae Juss. in Paraná, Brazil - Völtz, Rafael R.; Alves-Araújo, Anderson; Goldenberg, Renato (Phytotaxa, 2020)
Sapotaceae is a large family of angiosperms which has predominantly tree species, and worldwide distribution in subtropical and tropical regions. The Neotropics are one of the greatest centers of diversity of Sapotaceae, and in Brazil, the family comprises 12 genera and 234 species, of which 103 species are endemic. We present here a taxonomic treatment for the native species of Sapotaceae from the State of Paraná, with an identification key, descriptions, geographic distribution, phenology, illustrations, and current conservation status for all taxa. Twenty-two species were documented in Paraná, belonging to seven genera. The richest genus was Pouteria with 11 species, followed by Chrysophyllum with five species and Pradosia with two species. The genera Diploon, Ecclinusa, Manilkara, and Sideroxylon have only one species each. Pouteria guianensis and Pouteria ramiflora are new records for the state. The Atlantic Rain Forest is the richest vegetation type with six genera and 13 species, followed by the Seasonal Forest with three genera and nine species. The Araucaria Forest and Cerrado have two genera each, the former with three species and the latter with two species. Out of 22 species, one has been mentioned as endangered (EN), one is vulnerable (VU), one is near threatened (NT), nine are least concern (LC), and ten have not been evaluated (NE).